Viral : the search for the origin of COVID-19 - Chan, Alina; Ridley, Matt (Harper, an imprint of HarperCollinsPublishers, 2021)
In this real-life detective story, a scientist and writer team up to try to discover how a virus whose closest relations live in bats in subtropical China somehow managed to begin spreading among people more than 1,500 kilometers away in Wuhan.